Determinants of corporate governance characteristics influencing price and non-price informative voluntary disclosures: evidence from Iran - Zandi Pour Joopari, GholamReza; Md. Taib, Fauziah; Ibrahim, Daing Nasir (University of Malaya, 2010)
Davani (2005) reported that one of the biggest problems facing the Iranian investors is the poor quality of annual reports which preclude comprehensive and effective analyses. Makhija and Patton (2004) also found that institutional block holders lower the extent of voluntary disclosure in the firms’ annual reports when they enjoy direct benefits of being in control (DBC), therefore, the minority group is being expropriated. Since the Iranian Commerce Code’s requirement on information disclosure for public firms is limited to releasing only fundamental financial statements, the amount of disclosure in the Iranian firms’ annual reports are largely voluntary in nature. It is reported that the extent of information disclosure is driven by the private motivation rather than satisfying the mandated disclosure requirements. Therefore, this study intends to determine the characteristics of corporate governance that influence the voluntarydisclosures in Iran in terms of their usefulness and effects on the share prices as Price Informative Disclosures (PID) and their non-usefulness as Non-Price Informative Disclosures (Non-PID). These characteristics may help investors by presenting underlying economic substance of public firms listed on the Tehran Stock Exchange as their true financial picture may be unattainable. This study aims at depicting the Iranian stock market in which low transparency comes with low level of public confidence that results in the reluctant behaviour of investors from the private sector to buy shares. The findings, in general, suggest that the listed firms provide the market with a moderate amount of information which consists mainly of Non-PID matters. The lack of confidence among investors from the private sector is due to low level of transparency and failure to present true financial positions.